Lesser-Known Papers by a Well-Known Researcher of Russian Society: Yury Levada’s Ideas on Economic Sociology - Markin, Maxim (Journal of Economic Sociology, 2018)
2016 marked the 10th anniversary of the death of a well-known researcher of the Russian society, Yury Levada. His book A Time of Changes: The Subject and Researcher’s Attitude was published to commemorate his work. The book consists of both well-known and lesser-known papers, including papers in economic sociology. In “Social Frames of Economic Action” (1980), Levada defines the subject of economic sociology, explains the role of the society and culture in the economy, and demonstrates the historicity of rationality. These ideas are developed in his “Cultural Context of Economic Action” (1984). In this paper, Levada points out that human needs are embedded into culture, whereas economic exchange is loaded by cultural meanings. In “Homo oeconomicus, or The Fate of a Phantom” (1977), the key characteristics of Homo oeconomicus and the prospective use of this model are highlighted. “The Problems of Economic Anthropology by K. Marx” (1983) also includes Levada’s reflections on the assumptions of Homo oeconomicus and the discrepancies between this model and real life. What makes Levada’s approach unique is that, on one hand, his ideas in economic sociology follow the tradition of the Soviet sociology (a complex mix of Marxism and structural functionalism). On the other hand, these ideas are developed to the micro level, close to the stream of the new economic sociology.